Executive Remuneration in Retrospect - Rahim, Hifza (2013)
The focus and purpose of this paper is to document the advancement and development of executive remuneration over the past thirty years. It attempts to provide a useful contribution towards the field of executive remuneration by producing a synthesis of the developments and academic endeavor that has occurred from a theoretical and empirical perspective. Agency problems arise when ownership and control are separated and the owners are unable to perfectly observe the actions of the manager (Shleifer & Vishny, 1997). As a result, executive pay packages are designed to provide the correct level of incentives to mitigate the creation of agency costs. From a theoretical perspective, an efficient pay package should eliminate agency costs. However, in practice it has been found that incentives are often misaligned leading to the gains of executives’ personal wealth at the expense of the shareholders’ wealth. Thus, agency costs and its elimination is an important focus of this paper. At the same time, it also documents the change and development of executive remuneration in the real world, outside the theoretical frameworks, where more often than not, it has been found to be inefficient. Therefore, through a timeline of executive pay over the last thirty years, this paper seeks to explore and analyse the root causes of agency costs and the failure of executive remuneration.